Tetrazine-mediated bioorthogonal prodrug–prodrug activation. Issue 36 (3rd August 2018) - Neumann, Kevin; Gambardella, Alessia; Lilienkampf, Annamaria; Bradley, Mark
Abstract : Prodrug–prodrug activation describes the simultaneous, traceless and bioorthogonal activation of two drugs. Abstract : The selective and biocompatible activation of prodrugs within complex biological systems remains a key challenge in medical chemistry and chemical biology. Herein we report, for the first time, a dual prodrug activation strategy that fully satisfies the principle of bioorthogonality by the symbiotic formation of two active drugs. This dual and traceless prodrug activation strategy takes advantage of theINV DA chemistry of tetrazines (here a prodrug), generating a pyridazine-based miR21 inhibitor and the anti-cancer drug camptothecin and offers a new concept in prodrug activation.